PENGARUH RETURN ON ASSET, NET PROFIT MARGIN, DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Amalia Ratna Puspa Wardani, Suprihatmi Sri Wardiningsih & Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
Food and beverage companies are one of the categories of consumer sectorcompanies that are currently growing and developing. The purpose of this study is toanalyze the effect of Return On Assets (ROA), Net Profit Margin (NPM), and EarningPer Share (EPS) on Stock Prices in Food and Beverage Sector Companies listed inIndonesia Stock Exchange Period 2014 – 2016. Types of samples used purposivesampling method. The number of samples in this study as many as 10 companies. Thetechnique of analysis is multiple linear regression. The results of this study show thatpartially show ROA and NPM have a positive but not significant influence on StockPrices, while EPS has a negative and insignificant influence on Stock Prices.Simultaneously show ROA, NPM and EPS have a significant influence on stock prices.Coefficient of determination given free variable that is ROA, NPM, and EPS todependent variable that is Stock Price equal to 25,5%. 74,5% influenced by other factoroutside of variable which studied.Keywords: ROA, NPM, EPS, Stock Price